Evaluation of antibacterial activity of crude extracts of Annona senegalensis (wild custard apple) against Staphylococcus aureus and Pseudomonas aeruginosa, and formulation of a topical gel - Johanna Govora; Marcia Matongorere; Rumbidzai Mangoyi (Infectious Diseases and Herbal Medicine)
Annona senegalensis is a plant well known as the wild custard apple and has been widely reported for its various medicinal uses. This study investigates the potential of Annona senegalensis extracts as antibacterial agents against common pathogenic bacteria Staphylococcus aureus and Pseudomonas aeruginosa. The leaves of Annona senegalensis were collected, dried, and ground into fine powder. The ground leaves were extracted using a soxhlet apparatus, and the solvents were methanol, ethyl acetate, and chloroform. A rotary evaporator was used to concentrate the extracts. Phytochemical analysis was carried out to investigate the phytochemicals present in different extracts of Annona senegalensis. The antibacterial activity of Annona senegalensis against Staphylococcus aureus and Pseudomonas aeruginosa was performed using the agar disc diffusion method. Ciprofloxacin was used as a positive control at different concentrations, and DMSO as a negative control. The topical gel was then formulated using Annona senegalensis leaf extracts, glycerine, and xanthan gum. The results show that Annona senegalensis leaf extracts of ethyl acetate, chloroform, and methanol contain saponins, flavonoids, tannins, glycosides, anthraquinones, terpenoids, steroids, phenol, and alkaloids. However, the ethyl acetate extract of Annona senegalensis exhibited the highest antibacterial activity compared to other extracts. Staphylococcus aureus was found to be the most susceptible. This study indicated that Annona senegalensis can effectively treat bacterial infections like wound infections associated with Staphylococcus aureus and Pseudomonas aeruginosa.